Energy and Urban Systems - Franzese, Pier Paolo; Lazarevic, David; †; Reddy, Sudhakara (Journal of Environmental Accounting and Management, 2026)
Energy and environmental security are major problems facing our global economy. Fossil fuels, particularly crude oil, are confined to a few regions of the world while the continuity of supply is governed by dynamic political, economic, and ecological factors. Cities and urban systems are largely dependent on local and imported resources in support of both quantitative and qualitative growth. However, modern cities are experiencing shortages of energy, water, clean air, social relations and cohesion, social inclusion, and ultimately lack of participatory governance of city complexity. At present about 50% of the world population (i.e., about 3.5 billion people) live in cities. The resource basis seems to be insufficient and unfairly distributed to support an acceptable standard of living for a large fraction of urban and rural population. In addition, the concentration of resources required to support cities places a huge load on surrounding environment. For these reasons, cities must face the challenge of reorganizing their infrastructures and lifestyles to cope with the decreasing availability of resources. The priority in policy making is to identify suitable policies to reorganize urban life in the presence of a shrinking resource basis. Such reorganization will have to make cities less energy and material demanding, although still providing high quality standards of life. This cannot occur without investments, research, and important and shared choices about lifestyles.